Seroprevalence and Vaginal Shedding of Herpes Simplex Virus Type 2 in Pregnant Adolescents and Young Women from Morelos, Mexico - Julio Cesar Muñiz-Salgado; Gabriela Juárez-De la Cruz; Dayana Nicté Vergara-Ortega; Santa García-Cisneros; María Olamendi-Portugal; Miguel Ángel Sánchez-Alemán; Antonia Herrera-Ortiz (Viruses, 2023)
Adolescents and young people are particularly vulnerable to contracting STIs, including HSV-2; furthermore, vaginal shedding of HSV-2 during pregnancy can cause vertical transmission and neonatal herpes. To evaluate the seroprevalence of HSV-2 and vaginal HSV-2 shedding in adolescent and young pregnant women, a cross-sectional study was carried out in 496 pregnant women—adolescents and young women. Venous blood and vaginal exudate samples were taken. The seroprevalence of HSV-2 was determined by ELISA and Western blot. Vaginal HSV-2 shedding was assessed by qPCR of the HSV-2 UL30 gene. The seroprevalence of HSV-2 in the study population was 8.5% (95% CI 6–11), of which 38.1% had vaginal HSV-2 shedding (95% CI 22–53). Young women presented a higher seroprevalence of HSV-2 (12.1%) than adolescents (4.3%), OR = 3.4, 95% CI 1.59–7.23. Frequent alcohol consumption was significantly associated with HSV-2 seroprevalence, OR = 2.9, 95% CI 1.27–6.99. Vaginal HSV-2 shedding is highest in the third trimester of pregnancy, but this difference is not significant. The seroprevalence of HSV-2 in adolescents and young women is similar to that previously reported in other studies. However, the proportion of women with vaginal shedding of HSV-2 is higher during the third trimester of pregnancy, increasing the risk of vertical transmission.